Induction of Protective Serum Meningococcal Bactericidal and Diphtheria-Neutralizing Antibodies and Mucosal Immunoglobulin A in Volunteers by Nasal Insufflations of the Neisseria meningitidis Serogroup C Polysaccharide-CRM197 Conjugate Vaccine Mixed with Chitosan - Huo, Zhiming; Sinha, Ruchi; McNeela, Edel A; Borrow, Ray; Giemza, Rafaela; Cosgrove, Catherine; Heath, Paul T; Mills, Kingston H. G; Rappuoli, Rino; Griffin, George E; Lewis, David J. M (Infection and Immunity, 2005)
Thirty-six healthy volunteers received either a single intramuscular injection of Neisseria meningitidis serogroup C polysaccharide (MCP)-CRM197 conjugate vaccine in alum or two nasal insufflations 28 days apart of the same vaccine powder, without alum, mixed with chitosan. Nasal immunization was well tolerated, with fewer symptoms reported than after intramuscular injection. The geometric mean concentrations of MCP-specific immunoglobulin G (IgG) after one nasal immunization were 3.25 [micro]g/ml in nai̊ve subjects and 14.4 [micro]g/ml in subjects previously immunized parenterally, compared with 4.30 [micro]g/ml in nai̊ve subjects immunized intramuscularly. The geometric mean titer of serum bactericidal antibody (SBA) rose 24-fold after two nasal immunizations in nai̊ve subjects and was comparable to parenteral immunization (1,080 versus 1,625). All subjects achieved SBA titers associated with protection after two nasal immunizations: even those with titers of <8 at entry. A single nasal immunization boosted the SBA titer to [>/=]128 in 96% of previously immunized subjects, and two immunizations achieved this level in 92% of naive subjects. MCP-specific IgG levels were [approximately]70% IgG2 and [approximately]20% IgG1 after nasal or intramuscular immunization. Increases in CRM197-specific IgG and diphtheria toxin-neutralizing activity were observed after nasal or intramuscular immunization, with balanced IgG1/IgG2 and higher IgG4. Significant MCP-specific secretory IgA was detected in nasal wash only after nasal immunization and predominantly on the immunized side. Simple nasal insufflation of existing MCP-CRM197 conjugate vaccines in chitosan offers an inexpensive but effective needle-free prime and boost against serogroup C N. meningitidis and diphtheria.